Evaluation for additional work of waterproofing on the retaining wall and capping beam of BRAC University new campus project - Brac University (Brac University, 2023)
This record consists of general correspondence regarding evaluation for additional work of waterproofing on the retaining wall and capping beam of BRAC University new campus project.